Public Participation in Rural Development Planning - Detha Riristuningsia; Wahyunadi Wahyunadi; Iwan Harsono (Universitas Negeri Malang, 2017)
This study aims at investigating the level of community participation in a rural development planning (Musrenbangdes) in Lapok village, and seeking the factors influencing the level of their participation. It is a qualitative study in which the data are generated through library research, in-depth interviews semi-structured with informants in the field and observations. Informants selected by purposive sampling with the scope of the informants are people who are involved and have a significant influence in the implementation of the Village Planning Forum activities ranging from the preparation, implementation and post-implementation activities. Finding shows the level of community participations in development planning through in the Village Planning Forum in Lopok village is still in the level of apparent (degmess of tekonism). This illustrates that the community involvement in these activities to the extent that new proposals and have no influence and power in determining the final decision. In addition, factors which affect the level of their participation are the low education levels, community work, weak leadership of the village head, lack of socialization and cooperation between communities and village government.Keywords: Participation, Development Planning, Community Participation, Participatory PlanningJEL Classification: O18, R11